Islamic Education Policy in Indonesia and Saudi Arabia: A Comparative Analysis of Philosophical, Legal, and Sociocultural Frameworks - Mokhamad Yaurizqika Hadi; Minatullah Minatullah; Firdausih Firdausih (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2026)
Islamic education policy plays a strategic role in shaping religious identity, governance, and social cohesion in Muslim-majority countries. Despite sharing Islam as a foundational reference, Indonesia and Saudi Arabia have developed distinct policy orientations shaped by divergent philosophical commitments, legal frameworks, and sociocultural contexts. Existing studies have primarily examined these systems in isolation or through a single analytical lens, leaving a limited comparative understanding of how multiple dimensions interact to shape Islamic education policy. This study addresses this gap by comparing Islamic education policies in Indonesia and Saudi Arabia through philosophical, juridical, and sociocultural perspectives. The study employed a qualitative-comparative approach based on library research. Data were collected from primary sources, including national education laws and official policy documents, as well as secondary sources such as peer-reviewed journal articles and academic books. Data were analyzed using qualitative content analysis to identify patterns of convergence and divergence across the three analytical dimensions. The findings reveal that Indonesia adopts an integrative and pluralistic model of Islamic education, combining Islamic values with a secular-constitutional framework that emphasizes religious moderation and social diversity. In contrast, Saudi Arabia implements a centralized and theologically uniform model grounded in Sharia-based governance and Salafi doctrinal orientation. Socioculturally, Indonesia’s multicultural context encourages adaptability, while Saudi Arabia’s relative homogeneity supports policy uniformity, albeit with gradual reforms under Vision 2030. This study contributes theoretically by proposing an integrative analytical framework that explains how philosophy, law, and sociocultural context jointly shape Islamic education policy. Practically, it offers insights for developing Islamic education systems that balance theological integrity with inclusivity and global educational demands.